Antibiotic-derived approaches in cancer therapy: effectiveness of ikarugamycin in hexokinase-2 inhibition, tissue factor modulation, and metabolic regulation in breast cancer - Akgül Obeidin, Serra Vildan; Şenol, Maşite Şehadet; Doğru Köseoğlu, Zeynep; Bayramoğlu, Feyza; Dişli, Sevgi; Yiğitbaşı, Türkan; Emekli, Neslin (My University, 2025)
We aimed to explore the role of ikarugamycin (IKA) in breast cancer, its connection with hexokinase-2 (HK-2) repression, and tissue factor (TF). This study sought to extend the role of HK-2 as a TF activator in a comprehensive analysis of these interactions from the enzyme, gene, and protein levels. The investigation was performed with MDA-MB-231 and MCF-7 breast cancer lines. The oxidative stress index (OSI), lactate production, and HK activity were assessed using colorimetric assays. Western blot and quantitative PCR analyses were performed to determine HK-2 and TF expressions. Prothrombin time Tests additionally assessed the effect of IKA therapy on TF activation. Three over four significantly downregulated genes were identified after a specific analysis of the IKA’s effect on HK-2 and TF in breast cancer cell lines. In the IKA treatment group, lactate production was markedly reduced (P < 0.05) and hexokinase activity was found to be reduced in all groups (P < 0.05, <0.01). Paclitaxel cytotoxicity independently causes lower OSI in all IKA-treated groups as compared to controls even though OSI is elevated in IKA groups compared to control. Molecular analysis results demonstrated significantly downregulated HK-2 and TF expressions at the protein level (P < 0.05, P < 0.01). Partial thromboplastin time results also showed that IKA-treated cells had longer TF activation duration. A potential indirect association of HK-2 inhibition and TF regulation in breast cancer cells is put forward in this study by presenting IKA’s bioactivation of breast cancer in all gene, protein, and enzyme levels.
Keywords: Anticancer Antibiotics; Breast Cancer; Cancer Metabolism; Hexokinase-2; Tissue Factor